Spacious Grammar: Agency and Intention in the Teaching of Research Writing - Thieme, Katja (Discourse and Writing/Rédactologie, 2022)
Standardized academic English is now understood to be rooted in histories and practices that are colonial, classist, nationalist, heteronormative, ableist, and sexist. Current teaching of academic English carries an ethos of making practices of research writing accessible to students from marginalized backgrounds through explicit attention to language patterns and genre structures. In the context of both ideological critique and explicit pedagogy, I discuss three pragmatic elements of research writing—positionality, citation, and evaluation—with examples from one of my courses. I present these elements and my approach to teaching them as a practice that is attentive to both details of published scholarship and students’ agency and intentionality in shaping their own writing projects, claims, and arguments. My work is framed by a functional approach to grammar where grammar is not interesting as a standardized apparatus but as a code that provides a range of options for producing performative effects. I call this spacious grammar.